The Existence of the Gili Mas Cruise Port to Support Sekotong Tourism - Uzunu Hairi Ismail; Komang Mahawira; Surayyal Hizmi (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
The Gili Mas cruise ship port has become a huge opportunity for developing tourism on the island of Lombok, especially Sekotong area which is a buffer area for the port. However, in its operations, in the last half decade, there has been no research examining the impact of the existence of the Gili Mas port in supporting tourism development in its buffer area. This research aims to explore the role and existence of the Gili Mas cruise ship port in supporting the tourism industry in the Sekotong area. The research method used is descriptive analysis, with data collected through surveys, literature studies, and interviews with 3 informants from the government industry, travel and the community as managers of the destination. The results of this research are that the presence of cruise ships does not show a high intensity of visits to destinations in the Sekotong area. This is demonstrated by direct interviews conducted with informants from both the government and destination managers. The aspects that influence this are in terms of the suitability of the destination to the preferences of cruise ship tourists, most of whom are elderly tourists, and the readiness of each destination in the Sekotong area to adapt to existing tourists. To be able to increase the number of tourist visits to Sekotong, there needs to be increased promotion and guarantees that the places to be visited in the area are safe in terms of accessibility, amenities and activities that can be carried out by elderly tourists who make up the majority on cruise ships